Functionalized Self-Assembled Monolayers: Versatile Strategies to Combat Bacterial Biofilm Formation - Pamela M. Lundin; Briana L. Fiser; Meghan S. Blackledge; Hannah L. Pickett; Abigail L. Copeland (MDPI AG, 2022)
Bacterial infections due to biofilms account for up to 80% of bacterial infections in humans. With the increased use of antibiotic treatments, indwelling medical devices, disinfectants, and longer hospital stays, antibiotic resistant infections are sharply increasing. Annual deaths are predicted to outpace cancer and diabetes combined by 2050. In the past two decades, both chemical and physical strategies have arisen to combat biofilm formation on surfaces. One such promising chemical strategy is the formation of a self-assembled monolayer (SAM), due to its small layer thickness, strong covalent bonds, typically facile synthesis, and versatility. With the goal of combating biofilm formation, the SAM could be used to tether an antibacterial agent such as a small-molecule antibiotic, nanoparticle, peptide, or polymer to the surface, and limit the agent's release into its environment. This review focuses on the use of SAMs to inhibit biofilm formation, both on their own and by covalent grafting of a biocidal agent, with the potential to be used in indwelling medical devices. We conclude with our perspectives on ongoing challenges and future directions for this field.